2015
DOI: 10.2298/gensr1503927v
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic abnormalities in lymphocytes evaluated with micronucleus assay in medical personnel occupationally exposed to ionizing radiation

Abstract: The aim of this study was to evaluate the genotoxicity of ionizing radiation on medical personnel using the micronucleus assay and to determine the human health risk. Paired Student?s t-test shows significant statistical difference between the total number of binucleated (BN) cells with micronuclei within the two groups (exposed and control) (t=6,812; p<0,05). The mean of MN frequencies in the exposed group increased in comparison with the mean of MN frequencies in the control group. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…In agreement with the positive genotoxic effects here observed, we found previously that zineb and Azzurro Ò induced chromosome aberrations, SCEs (Soloneski et al, 2001), and MNs in human peripheral blood lymphocytes in vitro (Soloneski et al, 2002a). In addition, structural chromosomal aberrations in CHO cells (Enninga, 1986) and MNs in human lymphocytes of agricultural workers in vivo (Pilinskaia, 1974) were also reported after zineb exposure. It has been reported previously by us that zineb most probably induces DNA damage via free radical reactions and production of reactive oxygen species (Soloneski et al, 2003b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with the positive genotoxic effects here observed, we found previously that zineb and Azzurro Ò induced chromosome aberrations, SCEs (Soloneski et al, 2001), and MNs in human peripheral blood lymphocytes in vitro (Soloneski et al, 2002a). In addition, structural chromosomal aberrations in CHO cells (Enninga, 1986) and MNs in human lymphocytes of agricultural workers in vivo (Pilinskaia, 1974) were also reported after zineb exposure. It has been reported previously by us that zineb most probably induces DNA damage via free radical reactions and production of reactive oxygen species (Soloneski et al, 2003b).…”
Section: Discussionsupporting
confidence: 90%
“…Similar responses were obtained in in vivo studies. Positive results were reported for lymphocytes from workers occupationally exposed to zineb, in which an increased frequency of structural chromosome aberrations was observed (Pilinskaia, 1974). Finally, in contrast to these studies, it was reported that zineb did not induce MNs in bone marrow cells of Wistar male rats after oral administration (Huntingdon Research Centre, 1985).…”
Section: Introductionmentioning
confidence: 94%
“…Micronuclei are generated due to exposure to genotoxic agents, especially IR [6,23]. Increased formation of small and large micronuclei, as an indicator of chromosomal instability, has been found in medical workers who are professionally exposed to IR [24].…”
Section: Micronucleus Assay (Procedures and Principles)mentioning
confidence: 99%